The interplay between the microbiome and the adaptive immune response in cancer development. (July 2016) - Russo, Edda; Taddei, Antonio; Ringressi, Maria Novella; Ricci, Federica; Amedei, Amedeo
The data from different studies suggest a bacterial role in cancer genesis/progression, often modulating the local immune response. This is particularly so at the mucosal level where the bacterial presence is strong and the immune system is highly reactive. The epithelial surfaces of the body, such as the skin and mucosa, are colonized by a vast number of microorganisms, which represent the so-called normal microbiome. Normally the microbiome does not cause a proinflammatory response because the immune system has developed different strategies for the tolerance of commensal bacteria, but when these mechanisms are impaired or new pathogenic bacteria are introduced into this balanced system, the immune system reacts to the microbiome and can trigger tumor growth in the intestine. In this review, we discuss the potential role of the bacterial microbiome in carcinogenesis, focusing on the direct and indirect immune adaptive mechanisms, that the bacteria can modulate in different ways.